1998
DOI: 10.1111/j.1945-5100.1998.tb01668.x
|View full text |Cite
|
Sign up to set email alerts
|

Secondary calcium‐iron‐rich minerals in the Bali‐like and Allende‐like oxidized CV3 chondrites and Allende dark inclusions

Abstract: Abstract-We have characterized Ca-Fe-rich silicates (salite-hedenbergite pyroxenes ( F s~o -~o W O~~-~O ) , andradite (Ca3Fe2Si3012), kirschsteinite (CaFeSiOd), and wollastonite (Ca3Si309)) in the type I chondrules and matrices in the Bali-like and Allende-like oxidized CV3 chondrites and Allende dark inclusions. In type I chondrules in the Bali-like CV3 chondrites, metal is oxidized to magnetite; magnetite-sulfide nodules are replaced by Ca-Fe-rich pyroxenes with minor andradite and pure fayalite. We infer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
88
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(104 citation statements)
references
References 34 publications
15
88
1
Order By: Relevance
“…Although our observations are consistent with a scenario in which the oxidized and reduced CV chondrites originated from the same, heterogeneously altered CV parent asteroid that experienced brecciation after alteration and lithification (Krot et al, , 1998a, the origin of the reduced and oxidized CV chondrites on separate asteroids cannot be excluded (M. Zolensky, pers. comm., 1999).…”
Section: Discussionsupporting
confidence: 77%
“…Although our observations are consistent with a scenario in which the oxidized and reduced CV chondrites originated from the same, heterogeneously altered CV parent asteroid that experienced brecciation after alteration and lithification (Krot et al, , 1998a, the origin of the reduced and oxidized CV chondrites on separate asteroids cannot be excluded (M. Zolensky, pers. comm., 1999).…”
Section: Discussionsupporting
confidence: 77%
“…Itoh and Tomeoka (2003) revealed that CO3 chondrites contain abundant dark inclusions (DIs), although they are smaller in size than those in CV3 chondrites. The DIs in the CO3 chondrites were found to be lithic clasts similar in mineralogy and chemistry to their host chondrites and that show evidence for aqueous alteration and subsequent dehydration, like DIs in CV3 chondrites (e.g., Kojima et al 1993;Kojima and Tomeoka 1996;Krot et al 1997Krot et al , 1998Ohnishi and Tomeoka 2002). This implies that the CO parent body once contained aqueous fluids and that there was a region (or regions) in the parent body in which aqueous alteration and subsequent dehydration took place.…”
Section: Nephelinization By Aqueous Alteration and Dehydrationmentioning
confidence: 86%
“…Under these conditions, melilite altered directly to phyllosilicate. The CM-chondrite style of alteration is different than that undergone by CO chondrites (which experienced fluid-assisted thermal metamorphism; e.g., McSween 1977; Scott and Jones 1990;Rubin 1998;Brearley 2006) or CV chondrites (which experienced oxidation and aqueous metasomatism; e.g., Krot et al 1995Krot et al , 1998aKrot et al , 1998bKrot et al , 2000Brearley 1999). …”
Section: Origin Of Spinel Inclusionsmentioning
confidence: 99%